Current prevalence of falciparum malarial infection among HIV patients on highly active antiretroviral therapy in university of Uyo teaching hospital, Uyo Nigeria - Amadi, Chijioke Patrick; Ikon, Grace Michael; Inyang, Udoinyang Clement (International Journal of Research in Medical Sciences, 2018)
Background: Malaria and HIV remain two leading causes of morbidity and mortality to patients in developing African countries. Both infectious diseases have been documented to account for an enormous morbidity and mortality in Sub-Saharan Africa. The geographical overlap in sub-Saharan Africa and South America has led to similarities in co-infection with Plasmodium and HIV, this has resulted in the quick progression and severity of both diseases particularly among the poor, and contributes to the poverty of sub-Saharan African nations by taking a toll on young people who contribute greatly to the workforce of the economy. The present study was conducted to determine the prevalence of malarial infection in HIV patients receiving high active antiretroviral therapy in university Uyo teaching hospital, Uyo Nigeria. Methods: A predesigned structured questionnaire was administered to collect bio data and socio-demographic characteristics from the participants consisting 35 HIV infected adult patients and 32 non HIV infected adults as controls. All HIV patients were receiving HAART during this study. The HAART regimens used by HIV infected patients consist of zidovudine, lamivudine, efavirenze, and nevirapine. Results: About 5 (14.2%) HIV patients on HAART had falciparum malaria. No falciparum malaria was detected in HIV negative participants. Of the five positive malaria cases detected in HIV patients, 8.5% were females and 5.7% were males. Conclusions: There was no significant difference of malaria parasite infection by gender (P = 0.88), age group (P = 0.17), and CD4+ count (O.R:1.0, P = 0.81).